2016
DOI: 10.1002/jmri.25217
|View full text |Cite
|
Sign up to set email alerts
|

Native myocardial longitudinal (T1) relaxation time: Regional, age, and sex associations in the healthy adult heart

Abstract: PurposeTo use magnetic resonance imaging (MRI) at two field strengths to assess healthy adults' regional myocardial noncontrast (native) T 1 relaxation time distribution, and global myocardial native T 1 between sexes and across age groups.Materials and MethodsIn all, 84 healthy volunteers underwent MRI at 1.5T and 3.0T. T 1 maps were acquired in three left ventricular short axis slices using an optimized modified Look–Locker inversion recovery investigational prototype sequence. T 1 measurements in msec were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
60
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 41 publications
15
60
3
1
Order By: Relevance
“…The lack of influence of age on the native T 1 and T 2 relaxation time values in our study could derive from the fact that, unlike in studies on adult populations, we analyzed only a small age range (11 years). 10,15,17 Mean T 1 relaxation time in children seems to be higher and T 2 relaxation time similar in comparison with those studies. 14 We have found that in children T 1 relaxation time was not influenced by sex, but T 2 relaxation time was higher in female than in male children.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The lack of influence of age on the native T 1 and T 2 relaxation time values in our study could derive from the fact that, unlike in studies on adult populations, we analyzed only a small age range (11 years). 10,15,17 Mean T 1 relaxation time in children seems to be higher and T 2 relaxation time similar in comparison with those studies. 14 We have found that in children T 1 relaxation time was not influenced by sex, but T 2 relaxation time was higher in female than in male children.…”
Section: Discussionsupporting
confidence: 86%
“…16 Until now, it was unknown whether pubertal status could influence T 1 and T 2 relaxation times. 15,16 We found no difference in T 1 and T 2 relaxation times between the studied group of boys and our adult reference group of middle-aged males. The lack of influence of age on the native T 1 and T 2 relaxation time values in our study could derive from the fact that, unlike in studies on adult populations, we analyzed only a small age range (11 years).…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations